Urgensi Materi Maqashid al-Syariah pada Mata Pelajaran PAI - Ade Dedi Rohayana (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
The present study tries to explain the urgency of ‘maqasid al-shariah’ materials in an Islamic Education subject and the endeavor that teachers attempt to incorporate the values ​​of maqasid al-shariah. Grounded in a qualitative descriptive approach, library research was conducted. Findings of the study promote that firstly, the urgency of maqasid al-shariah-based learning materials in Islamic education is to embed good thoughts and understanding to students concerning the main objectives of establishing Islamic law, i.e., maintaining religion, soul, reasoning, descendants, and property. These five pillars constitute the substance of the teachings of the Qur’an and the Hadith in countering students committing religious intolerance and radicalism. Secondly, Islamic education teachers attempt to internalize the values ​​of maqasid al-shariah to students. It suggests that the teachers should be able to understand the concept of maqasid al-shariah as the main objectives of Islamic tenets provided in Islamic education materials and to master the concept of ‘sabab al-nuzul’ (cause of revelation) of a Qur’anic verse or ‘sabab al-wurud’ (occasion of occurrence) of a hadith to interpret and convey the Qur’anic verses or Hadith not only at the textual level, but also the context one. Likewise, Islamic education teachers are supposed to have sufficient knowledge of the interpretation of the al-mu’tabar (admittedly legitimate) Qur’an so as to provide a comprehensive understanding of the wisdom of al-tasyri’ leading to the maqasid al-shariah.